Pengaruh Teamwork dan Komunikasi terhadap Kinerja Karyawan pada PT. Telkom Satelit Indonesia - Adeva Nirmala Rosyid (Jurnal Manajemen, Bisnis dan Kewirausahaan, 2025)
This study aims to obtain information regarding the influence of teamwork and communication on employee performance at PT Telkom Satelit Indonesia. Employee performance is one of the crucial factors that determine the productivity and success of a company, so understanding the factors that influence it is important. The method used in this study is a quantitative method with a survey approach. Data were collected through distributing questionnaires to 96 respondents who are permanent employees in one of the company’s operational divisions. The data analysis technique used is multiple linear regression with the help of SmartPLS 3.0 software. The results of the analysis show that teamwork and communication simultaneously have a significant influence on employee performance. Partially, both variables also show a positive and significant influence on performance. The adjusted R square value of 0.652 indicates that 65.2% of the variation in employee performance can be explained by teamwork and communication variables. Thus, these two variables have a very strong influence in improving employee performance. Meanwhile, the remaining 34.8% is explained by other factors not discussed in this study. These findings provide important implications for company management in managing human resources, particularly in strengthening teamwork and the effectiveness of internal communication. Therefore, it is recommended that companies continue to enhance synergy and collaboration among employees through activities that strengthen teamwork and establish open, efficient, and two-way communication systems. This is expected to create a work environment that supports increased productivity and optimally achieves the organization’s strategic goals.